2018
DOI: 10.1007/s10916-018-0907-8
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Autonomic Modulation Device to Control Training Performance after High-Intensity Interval Training Program

Abstract: The aim of the present research was to analyze the autonomic response in a group of trained swimmers before and after conducting a 4-week period of high-intensity interval training (HIT). Heart rate variability was analyzed in 14 swimmers (16.2 ± 2.6 years, 169.1 ± 10.2 cm and 61.3 ± 9.9 kg) in basal condition and during a HIT session before and after completing a training period. The HIT session that was evaluated consisted of: 16 × 25 m maximum speed, resting 30 s between sets. Participants combined aerobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 44 publications
3
19
0
1
Order By: Relevance
“…Regarding the autonomic modulation domain analysis, we found a different sensibility in the three HRV analysis models used, being the temporal domain (RMSSD and pNN50) and the nonlinear domain (SD1) parameters, the most effective to find modifications in autonomic modulations. This result improves the knowledge about HRV monitoring in the line with previous studies that found how the sensitivity of HRV domain analysis depends on the population analysed 36 41–45…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the autonomic modulation domain analysis, we found a different sensibility in the three HRV analysis models used, being the temporal domain (RMSSD and pNN50) and the nonlinear domain (SD1) parameters, the most effective to find modifications in autonomic modulations. This result improves the knowledge about HRV monitoring in the line with previous studies that found how the sensitivity of HRV domain analysis depends on the population analysed 36 41–45…”
Section: Discussionsupporting
confidence: 89%
“…Soldiers performed 2 Squat Jump (SJ), 2 Contramovement Jump (CMJ), and 2 Abalakov jump (ABK) following the procedure conducted in previous research (Clemente‐Suárez, González‐Ravé, & Navarro‐Valdivielso, ; Delgado‐Moreno, Robles‐Pérez, Aznar, & Clemente‐Suarez, ) Isometric handgrip strength by a grip dynamometer (Takei Kiki Koyo, Japan). In addition, head rate variability was recorded by a polar v800 HR monitor (Polar Electro Oy, Finland) validated to analyse RR function to analyse HRV (Giles, Draper, & Neil, ). We follow previous procedures (Belinchon‐deMiguel & Clemente‐Suárez, ; Beltrán‐Velasco, Bellido‐Esteban, Ruisoto‐Palomera, & Clemente‐Suárez, ; Clemente‐Suárez & Arroyo‐Toledo, ) analysing (a) 20 min of HRV while participants were waiting in waiting area previous to the simulation as a HRV baseline, and (b) the entire simulation. We used Kubios HRV software (University of Kuopio, Kuopio, Finland) to analyse the HRV data.…”
Section: Methodsmentioning
confidence: 99%
“…In this line, the sympathetic activation presented by the Paralympic athlete since the previous moments of the race showed an anticipatory anxiogenic response, also during the race an increase in sympathetic response was observed, as previous studies conducted in mountain ultraendurance runners [14], but with lower values of RMSSD, showing a higher impact of the ultraendurance race for the Paralympic athlete. The HRV seems to be an important tool to control, asses and predict sport performance, especially in ultraendurance events, since previous studies could differentiate fastest and lowest athletes in this probe only using this parameter [49], and it has been identified as an efficiency tool to control workload during training and physiological response in extreme ambient as well [50].…”
Section: Psychophysiological Measurementsmentioning
confidence: 99%